농지은행 기능 및 농지신탁제도에 관한 연구 - 김홍상 (한국농촌경제연구원, 2003)
A study on the Introduction of Farmland Banking and Trusting System in Korea The current situation of DDA agricultural negotiation under the WTO system strongly urges Korean government to open more positively agricultural product market, especially rice market, which will result in the decrease in the profitability of rice industry and the rapid decrease in demand and price of farmland. Rice fields have used most of farmlands and the farmland has been the most important asset of farmers in Korea. Farmland market and farmers' economy shall be thrown into confusion by the sharp decline in farmland demand and price. These changes in farmland price have required to introduce a new farmland management system that is very different from the existing ones. The main purpose of this research is to review the possibilities for introducing farmland banking and trusting system as a new farmland management system and a few policy issues surrounding it. This research shows the reasons why the introduction of farmland banking and trusting system is necessary, and they can be summarized as follows : (1) Korean government should take a measure to stabilize the farmland market, the situation of which will get worse, and may get into a vicious circle of “decrease in farmland price ⇒ increase of farmland to be sold ⇒ increase of bargain sale of farmland ⇒ sharp decline in farmland price ⇒ increase of bankruptcy of farm and related banks”, (2) it should make the rice industry competitive by improving the existing farmsize through ‘farmsize increasing projects’ and restructuring the industry, and (3) it should cope with the diverse and increasing demand for farmland to empower and enterprise rural community etc. American and French experiences show severe problems of sudden decrease in price and confusion of farmland market. But it will not happen and the decrease of farmland price can play positive role in restructuring rice industry if farmland banking and trusting system is introduced to Korea and mobilizes the farmland more actively than before. Farmland banking and trusting system can be introduced a little more easily by putting the roles of farmland banking(buying, selling, lending, trusting, holding, reserving, etc.) onto the KARICO(Korea Agricultural and Rural Infrastructure Corporation) that has managed the ‘farmsize increasing projects’. There are several policy issues for introducing this kind of new system : fundraising, taking legal steps for realizing new programs, harmonizing with other programs, reforming the practicing systems of the related policy programs(for example, farmsize increasing project), etc. Researcher: Kim Hong-Sang E-mail Address: hskim@krei.re.kr